PERAN KEORANGTUAAN GURU DAN KONTRIBUSINYA TERHADAP PEMBENTUKAN SIKAP SOSIAL SISWA MADRASAH IBTIDAIYAH - Harmonis, Mistria; Nisak, Alfi Khoirin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article aims to describe and critically analyze the parental role of teachers and its contribution to the formation of students’ social attitudes in Islamic primary education. The study employed a qualitative approach using a case study design. The research was conducted at MI Islamiyah Syafi’iyah Gasal, Kotaanyar Sub-district, Probolinggo Regency, over a period from October to Desember 2025. Data were collected through participant observation, in-depth interviews, and document analysis. Data analysis followed the Miles and Huberman qualitative analytical framework, consisting of data reduction, data display, and conclusion drawing. The findings reveal that the parental role of teachers in shaping students’ social attitudes is manifested through several interrelated dimensions: teachers acting as parental figures within the school environment, teachers serving as role models of social exemplarity, the implementation of structured socio-religious habituation, the internalization of social attitudes through daily social interactions, and the use of communicative and dialogical approaches that strengthen students’ social awareness. These findings underscore the strategic importance of teachers’ parental roles in fostering socially responsible and morally grounded behavior among students in Islamic primary schools.